A study on factors that influence zakat payment among Muslim staffs at Amanah Raya Berhad Masjid Jamek, Kuala Lumpur / Azaimah Abdul Rahman - Abdul Rahman, Azaimah (Faculty of Business and Management, 2015)
This paper is aimed to investigate the factors that influenced zakat payment among Muslims. The factors that influenced zakat payment among Muslims are self-satisfaction, level of knowledge and level of income. The objectives of this study are to identify the relationship between the self-satisfaction, level of knowledge and level of income with zakat payment among Muslims. Next, the purpose is to identify the most significant factors that influence zakat payment among Muslims. Primary data of this study are by distributing the questionnaires. In gathering the data, 100 sets of questionnaires are distributed to Muslims staffs at Amanah Raya Berhad. All of the questionnaires were answered and returnable. The reliability test, descriptive analysis, and regression method are used for the data analysis. The Regression Method is used to analyze the relationship between dependent variables and independent variables and to identify the most significant variable. The findings show that all three (3) variables managed to have a significant result towards the dependent variable which is zakat payment among Muslims and can be used in making predictions in this study. It is concluded that level of knowledge is the most significant factor that influence zakat payment among Muslims and it is recommended that future research on similar topics that focus on rural or urban area or another company should be conducted.